Current surgical practice for multi-level degenerative cervical myelopathy: Findings from an international survey of spinal surgeons. (May 2021) - Davies, Benjamin M.; Francis, Jibin J.; Butler, Max B.; Mowforth, Oliver; Goacher, Edward; Starkey, Michelle; Kolias, Angelos; Wynne-Jones, Guy; Hutton, Mike; Selvanathan, Senthil; Thomson, Simon; Laing, Rodney J.C.; et al.
Highlights: Degenerative cervical myelopathy is a major cause of disability. Surgery is the mainstay of treatment, but there is significant variation in approach. This was an international survey of spine surgeons. We found that approach is decided on a case by case basis. However, posterior approaches are favoured. Further study required to assess need for fusion in addition to laminectomy. Abstract: Degenerative cervical myelopathy (DCM) results from compression of the cervical spine cord as a result of age related changes in the cervical spine, and affects up to 2% of adults, leading to progressive disability. Surgical decompression is the mainstay of treatment, but there remains significant variation in surgical approaches used. This survey was conducted in order to define current practice amongst spine surgeons worldwide, as a possible prelude to further studies comparing surgical approaches. Methods: An electronic survey was developed and piloted by the investigators using SurveyMonkey. Collected data was categorical and is presented using summary statistics. Where applicable, statistical comparisons were made using a Chi-Squared test. The level of significance for all statistical analyses was defined as p < 0.05. All analysis, including graphs was performed using R (R Studio). Results: 127 surgeons, from 30 countries completed the survey; principally UK (66, 52%) and North America (15, 12%). Respondents were predominantly Neurosurgeons by training (108, 85%) of whom 84 (75%) reported Spinal Surgery as the principal part of their practice. The majority indicated they selected their surgical procedure for multi-level DCM on a case by case basis (62, 49%). Overall, a posterior approach was more popular for multi-level DCM (74, 58%). Region, speciality or annual multi-level case load did not influence this significantly. However, there was a trend for North American surgeons to be more likely to favour a posterior approach. Conclusions: A posterior approach was favoured and more commonly used to treat multi-level DCM, in an international cohort of surgeons. Posterior techniques including laminectomy, laminectomy and fusion or laminoplasty appeared to be equally popular.